Violent proletarianisation: Social murder, the reserve army of labour and social security 'austerity' in Britain. (August 2019) - Grover, Chris
This article examines social security policy for working age people in Britain in the 'age of austerity'. Drawing upon critical approaches to understanding social policy and violence, the article argues that severe cuts to benefits and the ratcheting up of conditionality for, and the sanctioning of, benefit recipients can be understood as 'violent proletarianisation' – using socio-economic inequality and injustice to force the commodification of labour power, and a consequential creation of diswelfares that are known and avoidable. The article suggests that violent proletarianisation is a contradictory process, one that helps constitute the working class, but in a way that socially murders some of its reserve army members.